Strategi Pemasaran Untuk Meningkatkan Volume Penjualan Sepeda Motor Pada CV Trio Motor Muara Teweh - Mtw, Erline (Sekolah Tinggi Ilmu Ekonomi Muara Teweh, 2020)
This study aims to determine the marketing concepts and strategies, if applied to the company. To find out the relationship between marketing strategies and sales volume. To find out what causes the problems that exist in the company Trio Motor Muara Teweh, especially in marketing. Can be used as a reference and scientific documentation ... This research method uses qualitative methods. Sampling technique is simple random sampling. With 32 respondents who are consumers of the Muara Teweh Motor Trio. Data Analysis Techniques SWOT Analysis and BCG Analysis (Boston Consulting Group). The results of data collection and conclusions obtained strength results from CV. Muara Teweh Motorcycle Trio is good product quality and the price is quite affordable, also a vast marketing area compared to other competitors. In the BCG portfolio matrix, Honda motorcycle products are in the